PARTICIPATION IN SPORTS-RELATED EXTRACURRICULAR ACTIVITIES: A STRATEGY THAT ENHANCES SCHOOL ENGAGEMENT - St-Amand, Jerome; Girard, Stéphanie; Hiroux, Marie-Hélène; Smith, Jonathan (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
This article outlines a strategy that we, as high school teachers, used in the academic year 2012-2013 to improve a student’s school engagement. Extracurricular activities such as sports have proven useful (among other strategies) to counter school disengagement, specifically in enhancing positive social relations among the teachers and students involved. The authors present an approach implemented in partnership with the students, and discuss the consequences of this strategy for the students and the desired improvements. Finally, we emphasize the importance of peer involvement, teachers’ collaboration, and the teachers’ willingness to inspire and empower change. PARTICIPATION À DES ACTIVITÉS PARASCOLAIRES SPORTIVES : UNE STRATÉGIE POUR SOUTENIR L’ENGAGEMENT SCOLAIRE Cet article porte sur une stratégie que nous avons mise de l’avant à titre de praticiens afin de susciter l’engagement d’un élève à l’école pendant l’année scolaire 2012-2013. Le recours à une activité parascolaire axée sur le sport pour favoriser l’engagement de l’élève s’est avéré en partie efficace pour contrer ce phénomène, notamment en suscitant la qualité des liens sociaux entre tous les acteurs impliqués. Les auteurs présentent la stratégie élaborée en partenariat avec l’élève, les retombées de celle-ci et les améliorations souhaitées. Finalement, ils soulignent l’importance de l’implication des pairs, de la collaboration entre les enseignants, et de la capacité des praticiens à inspirer et à susciter du changement chez les élèves.